The Influence of E-Books Through a Differentiation Approach Assisted with Professional Pageflip 3-Dimensions on Student Learning Outcomes on Simple Machines Topic - Gimnastiar, Asih Nurbaiti; Abdjul, Tirtawaty; Nurhayati, Nurhayati; Odja, Abdul Haris; Yusuf, Muhammad; Payu, Citron S. (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
This research aims to test the effect of e-books through a differentiated approach assisted by page flip professional 3-dimensions on student learning outcomes on simple machine topics. The research uses a pre-test and post-test control group design involving two classes as samples. Using e-books through a differentiated approach can reduce the problem of unequal distribution of printed books and make it possible to adapt them to each student's learning style because each student has their learning style. This is shown through the hypothesis criteria where the significance value of 0.030 is smaller than the significance level of 0.05, so H0 is rejected, and Ha is accepted. This is also supported by acquiring an N-gain Score value of 0.81 in the experimental class, which meets the high category, and in the control class, 0.51, which meets the medium category. For the N-gain percent interpretation category, the results obtained in the experimental class were 81 in the effective interpretation category, while for the control class, the results were 51 in the less effective interpretation category. This indicates that e-books, through a differentiated approach assisted by page flip professional 3-dimensions, can improve student learning outcomes, especially in simple machine topics. This research concludes that e-books, through a differentiated approach assisted by page flip professional 3-dimensions, can be an effective alternative for improving the quality of science learning in schools.